An Automatic Localization Tool for Null Pointer Exceptions - Jing Duan; Shujuan Jiang; Qiao Yu; Kai Lu; Xu Zhang; Yiwen Yao (IEEE Access, 2019)
Null pointer exceptions are common software faults, but they are dangerous and can cause a program to crash if they occur. In addition, it is hard to find them by simply running test cases. When a null pointer exception occurs, the stack trace stored by the Java runtime environment can help us to locate the cause of the exception. In this paper, firstly, we propose an automatically null pointer exception localization approach guided by stack trace, from the null pointer dereference to the null value assignment point. Secondly, an empirical study is designed to evaluate the effectiveness of the tool on eight open source projects. The experimental results show that the tool is effective in locating the null pointer exception.